Text in modeling the language consciousness of foreign students - Zlotnyk-Shagina, Olga (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article considers the text as the main tool in the process of learning the Ukrainian language for foreign students. The text helps not only in learning the foreign language, but also in learning the mentality and the formation of intercultural competence. That is why the initial postulate of the theory of linguistics in Ukraine is the focus on the study of Ukrainian culture in the process of learning the language through various media and sources of national and cultural information, for example, through the text. For this purpose, texts and tasks for them have been developed, which will later be included in the educational and methodological development intended for foreigners studying the Ukrainian language. The article presents a classification of tasks that accompany the texts by stages of their implementation and examples of such tasks for the rapid study of Ukrainian as a foreign language. The main task of a teacher of Ukrainian as a foreign language is to make the most of the material of the textbook for the development of grammar and language skills and abilities of students, because they need to encourage them to express themselves and prepare for natural communication. The purpose of training always determines the choice of methods. For foreigners studying the Ukrainian language, the motivation is mainly constructive communication with Ukrainian-speakers, official correspondence in the Ukrainian language, i.e. professional activity. And in this aspect, the creative approach to working with the text is an effective solution to educational problems, which is based on the analysis of the relationship between language and speech, speech and thinking, thinking and communication. Therefore, the article presents a practical part of working with the text to learn the Ukrainian language. The textbook for learning Ukrainian as a foreign language is not only a means of teaching foreign students to read in Ukrainian, but also a great opportunity to form and develop their speaking, listening and writing skills, so in the arsenal of every teacher of Ukrainian as a foreign language should be different texts which correspond to the cultural theme as well as the interests and abilities of students.
Keywords: text, language consciousness, study of the Ukrainian language as a foreign language, original text, adapted text, types of text tasks.